PERBEDAAN HASIL BELAJAR SIMULASI DIGITAL SISWA YANG DIAJAR DENGAN METODE KONVENSIONAL DAN METODE PRAKTIK LANGSUNG DI KELAS X SMK NEGERI 1 BENGKULU SELATAN - Hidayatullah, Ade; Yul, Fadlul Amdhi; Susanto, Edy (Journal Of Dehasen Educational Review, 2022)
The purpose of this paper is to determine the differences in learning outcomes of digital simulations using conventional learning methods and direct practice in class X SMK Negeri 1 Bengkulu Selatan. This research is a type of quantitative approach research. The population in this study were all class X DKV 1 and X DKV 3 SMK Negeri 1 Bengkulu Selatan. The sample used in this study, namely class X DKV 1 as experimental class 1 and X DKV 3 as experimental class 2. The sample consisted of 30 students. This research uses observation method, test method. Observation is used for observation or recording of objects at SMK Negeri 1 Bengkulu Selatan. The test method was used to determine differences in student learning outcomes of class X SMK Negeri 1 Bengkulu Selatan. The results of this study show student learning outcomes in Digital Simulation subjects taught with Conventional Methods and Practical Methods. It is known from the table that the average value (Mean) 85.00 and the Standard Deviation value ( Std. Deviation ) is 4.226 for the results. learn Digital Simulation students who are taught by the Direct Practice Method (X DKV 1), while the average value (Mean) is 80.33 and the Standard Deviation value ( Std. Deviation) 3,994 for the Digital Simulation learning outcomes of students who are taught using the Conventional Method (X). DKV 3). Keywords: Difference, Learning Outcomes, Digital Simulation